Hi guys,
SO I've come to ask a simple math question, the answer doesn't perplex me but rather surprises me slightly.
so (k/6)(k+1)(2k+1) = (k+1/6)(k)(2k+1)
let's call (k/6)(k+1)(2k+1) A and (k+1/6)(k)(2k+1) B for simplicity.
let's just focus are concern on (k/6)(k+1) as (2k+1) will be the constant in this scenario or maybe redundant would be more precise.
What surprises ms is that (k/6)(k+1) = (k+1/6)(k).
I know that multiplication is obviously both associative and commutative, so
|
(2 * 3) * 6 == 2 * (3 * 6) and also (2)(3)(8) == (3)(8)(2) == (8)(2)(3) and so on
|
but division isn't neither commutative or associative so how does A == B
let's try 2 test cases, let's set k = 2 and 5 respectively.
let's first test A with k = 2,
(2/6)(2+1)(2(2)+1)
(1/3)(3)(5)
(1)(5) = 5
let's now test B with k = 2,
((2+1)/6)(2)(2(2)+1)
(3/6)(2)(5)
(0.5)(2)(5)
(1)(5) = 5
Now let's set k = 5,
(5/6)(5+1)(2(5)+1)
(5/6)(6)(11)
(5)(11) = 55
now B
((5+1)/6)(5)(2(5)+1)
(6/6)(5)(11)
(5)(11) = 55
so they both clearly equal one another but what law or rule allows this to hold true?